Outcome of Laparoscopic Pyeloplasty for Ureteropelvic Junction Obstruction: Experience With 13 Cases (Bangladesh Journal of Urology, 2020)
Background: Open pyeloplasty has been the gold standard for surgical treatment ofureteropelvic junction (UPJ) obstruction, enjoying a long-term success rate exceeding90%. Unfortunately, this procedure requires a muscle incision that entails some degreeof morbidity. We have, therefore, investigated the feasibility of laparoscopic pyeloplastyfor UPJ obstruction and report here the outcomes of our early cases. The median followupwas 21 months (range, 12–30 months).Objectives; The aim of our study was to explore the safety, feasibility and usefulness oflaparoscopic pyeloplasty and to assess the short- term outcome of patients treated withthis surgical approach.Materials and methods: This study was performed on 13 patients presenting withsymptomatic hydronephrosis, secondary to UPJ obstruction at the Department of Urology,Shahid Sheik Abu Naser Specialized Hospital, Khulna from January 2015 to June 2017.Patients having previous abdominal surgery and sepsis were excluded from this study.Laparoscopic dismembered Anderson–Hynes pyeloplasty was performed in all cases.All procedures were carried out transperitoneally.Results: All procedures were laparoscopically completed with no open conversion. Meanoperative time was 272.8 min (range, 175–480 min) and blood loss was minimum. Meanhospital stay was 4.5 days (range,4-11 days). Anomalous vessels were identified in 5patients. Post-operative complications were noted in two patients (15.4%): one instanceof prolonged urine leakage and one anastomotic re-stricture. Twelve of 13 ureters (92.3%)demonstrated a patent UPJ on excretory urography and split renal function and GFRwere significantly improved (p